Sharia in Moroccan Law: a perpetual source and guiding reference - Souad Ezzerouali; Mohamed Cheikh Banane; Brahim Hamdaoui (Faculty of Law, University of Muhammadiyah Malang, 2025)
This study examines the role of Sharia in the Moroccan legal system, assessing whether it serves as a fundamental source of legislation or merely a reference. Morocco's legal framework uniquely combines Islamic principles with secular laws, reflecting its colonial history and modern reforms to preserve Islamic heritage while advancing legal modernization. This distinctive blend positions Morocco as a model for balancing tradition and contemporary legal requirements. The research adopts a critical analytical approach, analyzing constitutional and legal texts, judicial precedents, and practical applications. It also conducts a comparative analysis with Indonesia to explore different approaches to integrating Sharia. Morocco applies Sharia centrally, especially in personal status laws, while Indonesia uses it regionally, such as in Aceh, within a predominantly secular national framework. The study highlights how historical, social, and political contexts influence the role of Islamic law in both countries. Findings show that Sharia is a crucial source for personal status matters in Morocco and a supplementary reference in other legal areas, with the Commander of the Faithful (Amir al-Mu'minin) maintaining this balance. In contrast, Indonesia emphasizes the regional application of Sharia alongside national secular laws. The study provides insights into balancing religious identity with legal modernization, offering a framework for legal pluralism that can inform researchers and policymakers in diverse socio-political contexts.